Researching Young People’s Sexualized Digital Practices Involving Imagery: : A Transmethodological Approach - Rasmussen, Penille Kærsmose Bøegh (Outlines. Critical Practice Studies, 2021)
Young people constitute and negotiate their gendered identities and belonging, as well as their romantic and erotic relationships, through sexualized digital practices involving imagery. Most of these practices are unproblematic, but sometimes they take forms that are more abusive and lead to (particularly) girls being visually exposed online. Such practices are commonly referred to as sexting or revenge pornography and have been subject to much discussion in research, in the media and among practitioners. These discussions, however, sometimes fail to acknowledge the diversity, volatility and ambiguity of the practices. This article discusses whether the approaches used in research on young people’s sexualized digital practices involving imagery are sufficiently refined and sensitive in order to grasp comprehensive complexity and messy constitutions of such practices. Based on analyses of the studies’ conceptualizations, perspectives and methods, I suggest that future research production might benefit from a more transgressive and flexible approach that learns from the full array of approaches in the previous studies and takes the instability and multiplicity of young people’s practices into account. Such an approach should entail an openness towards ambiguous conceptualizations, a more processual perspective that includes both individual, social and technological aspects and the use of multiple explorative methods across on- and offline spaces.